Comparison of the Effectiveness of group Dialectical Behavior Therapy with group Schema Therapy on Psychological Distress in Women with Coronary Heart Disease - Mohammadi Lapvandani, Golriz; Karbalaei Mohammad Migooni, Ahmad; Malihialzackerini, Saeid; Kalhornia Golkar, Maryam (Applied Family Therapy Journal (AFTJ), 2022)
Aim: This study aimed to compare the effectiveness of group dialectical behavior therapy with group schema therapy on psychological distress in women with coronary heart disease. Method: This was a quasi-experimental study using a pre-test-post-test design with a control group. The statistical population included women suffering from coronary heart disease referred to Azadi Hospital in Tehran in 2018-2019, 45 people were selected as a statistical sample by available sampling method and divided into two experimental groups, and one control group (15 people for each group) were replaced. The research measurement tools included psychological distress (Kessler et al., 2002). After completing eight sessions of dialectical behavioral therapy (two sessions per week for 4 weeks) and eight sessions of group schema therapy (two sessions per week for 4 weeks) in the experimental groups, the questionnaires were repeated immediately and after three months. The sequence was completed as a post-test and follow-up in groups. The results were analyzed using descriptive statistics and inferential (repeated measures analysis of variance) in SPSS.23 software. Results: The results of repeated measures analysis of variance showed that both treatments were effective on psychological distress in women with coronary heart disease from pre-test to post-test and follow-up (p=0.001). The Bonferroni post hoc test results also showed that group dialectical behavior therapy has a more significant effect on reducing psychological distress in women with coronary heart disease than group schema therapy from pre-test to post-test and follow-up (p=0.001). Conclusion: Therefore, group dialectical behavior therapy training is recommended as an effective intervention method for reducing psychological distress in women with coronary heart disease.